'Browning' the cardiac and peri-vascular adipose tissues to modulate cardiovascular risk. (1st February 2017) - Aldiss, Peter; Davies, Graeme; Woods, Rachel; Budge, Helen; Sacks, Harold S.; Symonds, Michael E.
Abstract: Excess visceral adiposity, in particular that located adjacent to the heart and coronary arteries is associated with increased cardiovascular risk. In the pathophysiological state, dysfunctional adipose tissue secretes an array of factors modulating vascular function and driving atherogenesis. Conversely, brown and beige adipose tissues utilise glucose and lipids to generate heat and are associated with improved cardiometabolic health. The cardiac and thoracic perivascular adipose tissues are now understood to be composed of brown adipose tissue in the healthy state and undergo a brown-to-white transition i.e. during obesity which may be a driving factor of cardiovascular disease. In this review we discuss the risks of excess cardiac and vascular adiposity and potential mechanisms by which restoring the brown phenotype i.e. "re-browning" could potentially be achieved in clinically relevant populations. Highlights: Epicardial, paracardial and thoracic perivascular adipose tissues resemble BAT at birth. Despite 'whitening' in early life these depots remain metabolically active and potentially thermogenic into adulthood. Obesity induces further 'whitening' and inflammation in these depots likely driving the atherogenesis. Maintaining or inducing the brown phenotype in these depots could prevent atherosclerotic disease.